Prospective evaluation of chronic rhinosinusitis with reference to anatomical variation - ., Sindhura; Kandipilli, Mamatha Devi; Shaik, Ali; Ramana, Venkata (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Rhinosinusitis is one of the commonest sinonasal condition with chronic Rhinosinusitis affecting 10% of population worldwide. Although the diagnosis of chronic rhinosinusitis is clinical, the final diagnosis should be confirmed by objective measures like radiography and nasal endoscopy. Though anatomical variations in sinonasal region are rare, they have significant impact in the causation of sinonasal diseases and pose difficulties during surgery. Methods: This was a prospective study conducted on 60 patients who attended to the Department of ENT and HNS, Konaseema Institute of Medical Science, Amalapuram between December 2017 to July 2019. By considering AAO-HNS criteria patients were selected and subjected to high resolution computerized tomography para nasal sinuses and diagnostic nasal endoscopy. Results: As per study, 60% patients are having deviated nasal septum, followed by aggar nasi in 58.3%, concha bullosa in 26.8%, Haller cells in 11.7%, paradoxical middle turbinate in 11.7%, uncinate pneumatisation in 5%, and onodi cells in 5% of cases. Conclusions: Anatomical variations in sinonasal cavity predispose to chronic rhinosinusitis and hence require correction. Also, detecting these variations preoperatively by computed tomography of paranasal sinus helps in avoiding complications during functional endoscopic sinus surgery.